2016
DOI: 10.1002/anie.201603844
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Identification of Spectral Properties and Sizes of Multiple Particles in Solution with Subnanometer Resolution

Abstract: We report on an unsurpassed solution characterization technique based on analytical ultracentrifugation, which demonstrates exceptional potential for resolving particle size in solution with sub-nm resolution. We achieve this improvement in resolution by simultaneously measuring UV-Vis spectra while hydrodynamically separating individual components in the mixture. By equipping an analytical ultracentrifuge with a novel multi-wavelength detector, we are effectively adding a new spectral discovery dimension to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 31 publications
(83 reference statements)
1
44
1
Order By: Relevance
“…Recently, it was demonstrated that MWL-AUC in combination with 2DSA can be used to determine the spectral properties and sizes of multiple but discrete quantum dot species. 37 Further studies shall be focused on MWL analysis to derive the size dependent extinction spectra for all species in polydisperse PSDs. AUC together with PCSA will then allow studying the quantum size effect for continuous distributions of semiconductor NPs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was demonstrated that MWL-AUC in combination with 2DSA can be used to determine the spectral properties and sizes of multiple but discrete quantum dot species. 37 Further studies shall be focused on MWL analysis to derive the size dependent extinction spectra for all species in polydisperse PSDs. AUC together with PCSA will then allow studying the quantum size effect for continuous distributions of semiconductor NPs.…”
Section: Discussionmentioning
confidence: 99%
“…SEDFIT, ULTRASCAN and SEDANAL offer a possibility for the analysis of this experiment type with special implemented methods. In ULTRASCAN and SEDANAL, it is even possible to analyze multiwavelength (MWL) data obtained by the MWL-detector (Karabudak et al 2016;Walter et al 2015). However, all analysis methods do not yet consider the difference in density created by the overlay solution.…”
Section: Introductionmentioning
confidence: 99%
“…The potential for MWL-AUC has drawn particular attention to the study of metallic and semiconductor nanoparticles, owing to the extraordinary size and shape dependent optical properties at the nano scale. AUC has the capability to resolve nanoparticle size distributions with Angstrom resolution, and with MWL detection, to also probe spectral properties in dispersion [16,17].…”
mentioning
confidence: 99%